Prediabetes; Prevention and Management: Prediabetes; Prevention and Management - Ali Mughal, Asad; Taha Abbas, Syed; Asad, Huma; Zubair, Muhammed; Ali Khan, Nasir; Naseem, Shehla; Zaman Shaikh, Muhammad (Pakistan BioMedical Journal, 2022)
Pre-diabetes is the state of hyperglycemia at an intermediate stage in which parameters of blood glucose are above standard value but less than the threshold of diabetes. Diabetes mellitus is measured as a risk factor with a high probability of its development. Although the analytic measures for pre-diabetes are not the same in different international professional organizations, the danger of diabetes development is still in height, with conversion rates ranging from 5% to 10% per year. Databased studies propose a relationship between diabetic complications and pre-diabetes like early kidney disease, early retinopathy, small fiber neuropathy and the danger of macrovascular disease. Numerous analyses have revealed the effectiveness of daily routine interpositions in preventing diabetes, with a comparative danger decrease of 40% to 70% in prediabetic adults. Though there is cumulative indication that drug therapy is effective in preventing diabetes in prediabetic adults, drug options for treatment rather than metformin are related with side effects that bound their usage in prediabetics. There are no studies of systematic assessment of the healthiness consequences associated with prediabetes among Children. The effect of pharmacology treatment of pre-diabetes on development and growth in children during adolescence is unidentified. Secondary involvement with metformin pharmacology treatment is recommended for speculative persons, but the standards for assessing the advantage of such primary interference, the longstanding cost-effectiveness of such treatment is still uncertain. Pharmacological treatment should be cast-off with care in prediabetic children. Although pre-diabetes is usually asymptomatic, pre-diabetes always occurs before diabetes develops. The high blood sugar level persists and therefore pre-diabetes cannot be considered completely mild. Conclusions: The purpose of this review is to define the difficulties related with the analysis of pre-diabetes, the potential adverse outcomes of pre-diabetes, and the treatment opportunities and validation of its practice in the context of pre-diabetes.